A slurry process for lithium ion battery cathode slurry

By employing a homogenization process involving the phased addition of specific solid content and repeated stirring, the problems of uneven dispersion and stability in lithium-ion battery cathode slurry were solved, achieving efficient slurry preparation and electrode consistency.

CN115888512BActive Publication Date: 2025-11-18コーネックス ニュー エナジー カンパニー リミテッド
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211493825.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-11-18
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

In the existing wet mixing process for lithium-ion battery cathode slurry, the conductive agent easily absorbs the solvent, resulting in uneven dispersion. The dry process is difficult to operate and has poor slurry stability, making it difficult to control the optimal state, which affects production efficiency and electrode consistency.

Method used

A homogenization process is adopted, in which positive electrode active material and conductive agent are added in stages with a specific solid content. The homogenization process involves multiple stirring and dispersion in a dual planetary mixer at a specific speed and vacuum, combined with a defoaming step, to prepare a uniform and fine slurry.

Benefits of technology

This achieves uniform dispersion of the positive electrode slurry, reduces the probability of agglomeration, improves the viscosity stability and solid content of the slurry, and enhances production efficiency and electrode consistency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888512B_ABST
    Figure CN115888512B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of lithium ion battery manufacturing process, and particularly relates to a kind of slurry process of lithium ion battery positive electrode slurry, sequentially comprising the following steps: S1: according to 5-7% solid content preparation glue solution, the whole binder and part of solvent in the positive electrode slurry are mixed to prepare glue solution, the glue solution is divided into three parts, respectively, first glue solution, second glue solution and third glue solution;S2: 23-27wt% of the total amount of positive electrode active material and all first conductive agent are added to the first glue solution to stir for the first time, then the second glue solution, all second conductive agent and 45-55wt% of the total amount of positive electrode active material are added to stir for the second time, finally the third glue solution, the remaining positive electrode active material and the remaining solvent are added to stir for the third time, and the positive electrode slurry is prepared.The slurry process of the present application makes the active particles of the positive electrode material more uniform and delicate, the probability of agglomeration is significantly reduced, the slurry viscosity is smaller, and the stability is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery manufacturing technology, specifically relating to a homogenization process for lithium-ion battery cathode slurry. Background Technology

[0002] In existing technologies, the homogenization of cathode slurry is generally divided into dry and wet processes. The dry process first premixes active materials, conductive agents, and other powdered substances at a certain speed. After mixing, a binder is added, and the mixture is stirred. Solvent is gradually added for further mixing and dispersion, and finally, a certain amount of solvent is added to dilute and adjust the viscosity to the required coating viscosity. The main process of the wet slurry preparation is to first mix and stir the binder, conductive agents, and other substances, then add the active material for thorough stirring and dispersion, and finally add an appropriate amount of solvent to adjust the viscosity to suit coating.

[0003] The problems with wet mixing processes are that the large surface area of ​​the conductive agent makes it easy to absorb the solvent, resulting in poor solvent flowability and making it difficult to achieve uniform dispersion after adding the active material. Dry mixing processes involve a kneading process, which is more difficult for operators to control. Furthermore, the viscosity of the slurry prepared by dry mixing is lower; the lower the viscosity, the shorter the time it takes to maintain stability, and the more prone it is to stratification. Secondly, controlling the optimal state of materials in dry pulping processes is difficult. Changes in raw material particle size, pH value, specific surface area, and other factors will alter the solid content at the optimal state, requiring process readjustment, which will affect production efficiency and the consistency between different batches of electrodes.

[0004] Patent publication number CN105552359A discloses a method for preparing a positive electrode slurry for lithium-ion batteries. The specific steps are as follows: solvent and binder are added to a vacuum mixer and stirred until homogeneous; a conductive agent is then added, followed by the addition of positive electrode active material in two batches for mixing; the positive electrode material is baked before mixing; during mixing, different speeds are used for stirring, along with vacuum stirring for a certain period; near the end of mixing, an appropriate amount of ethanol defoamer is added, and the slurry is filtered through a 100-mesh sieve before coating. However, the conductive graphite and carbon nanotubes are added all at once, which does not fundamentally solve the problem of their tendency to agglomerate and disperse unevenly. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the present invention aims to provide a homogenization process for lithium-ion battery cathode slurry.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a homogenization process for a positive electrode slurry of a lithium-ion battery, wherein the positive electrode slurry includes a positive electrode material and a solvent, and the positive electrode material includes a positive electrode active material, a first conductive agent, a second conductive agent and a binder;

[0008] The homogenization process includes the following steps in sequence:

[0009] S1: Prepare a glue solution (pre-applied glue) with a solid content of 5-7% (e.g., 5.25%, 5.5%, 5.75%, 6%, 6.25%, 6.5%, 6.75%). Mix all the binder in the positive electrode slurry with a portion of the solvent to prepare the glue solution. Divide the glue solution into 3 parts, namely the first glue solution, the second glue solution and the third glue solution.

[0010] S2: Add 23-27 wt% (e.g., 24 wt%, 25 wt%, 26 wt%) of the total positive electrode active material and all of the first conductive agent to the first adhesive solution and stir for the first time. Then add the second adhesive solution, all of the second conductive agent and 45-55 wt% (e.g., 46 wt%, 47 wt%, 48 wt%, 49 wt%, 50 wt%, 51 wt%, 52 wt%, 53 wt%, 54 wt%) of the total positive electrode active material and stir for the second time. Finally, add the third adhesive solution, the remaining positive electrode active material and the remaining solvent and stir for the third time to obtain the positive electrode slurry.

[0011] In the above-mentioned homogenization process of lithium-ion battery cathode slurry, as a preferred embodiment, in step S1, the slurry is prepared with a solid content of 5.2% to 6.3% (e.g., 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.0%, 6.1%, 6.2%).

[0012] In the above-mentioned homogenization process of lithium-ion battery cathode slurry, as a preferred embodiment, the theoretical solid content of the cathode slurry is 60-66% (e.g., 61%, 62%, 63%, 64%, 65%); preferably, the cathode material comprises: 1.5-2.5 wt% binder (e.g., 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2.0 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%), and 0.2-1.0 wt% first conductive agent (e.g., 0.3 wt%, 0.4 wt%). 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%), 0.2-1.0wt% of the second conductive agent (e.g., 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%), and 96-97wt% of the positive electrode active material (e.g., 96.1wt%, 96.2wt%, 96.3wt%, 96.4wt%, 96.5wt%, 96.6wt%, 96.7wt%, 96.8wt%, 96.9wt%).

[0013] In the above-mentioned homogenization process of lithium-ion battery positive electrode slurry, as a preferred embodiment, the binder is PVDF; preferably, the solvent is NMP (N-methylpyrrolidone); preferably, the first conductive agent is super-P; preferably, the second conductive agent is carbon nanotube NMP conductive slurry, and the solid content of the NMP conductive slurry is 1-10% (e.g., 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%); preferably, the positive electrode active material is lithium iron phosphate or lithium nickel cobalt manganese oxide.

[0014] In the above-mentioned homogenization process of lithium-ion battery cathode slurry, as a preferred embodiment, the mixing or stirring is carried out in a dual planetary mixer; preferably, the mixing is carried out at a stirring speed of 75-85 rpm (e.g., 76 rpm, 77 rpm, 78 rpm, 79 rpm, 80 rpm, 81 rpm, 82 rpm, 83 rpm, 84 rpm) and a dispersion speed of 4400 rpm-4600 rpm (e.g., 4450 rpm, 4500 rpm, 4550 rpm) for 90-120 min (e.g., 95 min, 100 min, 105 min, 110 min, 115 min); preferably, the volume ratio of the first, second, and third slurries is (0.8-1.2):(0.8-1.2):1; more preferably, it is 1:1:1.

[0015] In the above-mentioned homogenization process of lithium-ion battery cathode slurry, as a preferred embodiment, in step S2, the first stirring is: stirring at a stirring speed of 75-85 rpm (e.g., 76 rpm, 77 rpm, 78 rpm, 79 rpm, 80 rpm, 81 rpm, 82 rpm, 83 rpm, 84 rpm) for 30-60 minutes (e.g., 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes); preferably, the second stirring is: stirring at a stirring speed of 75-85 rpm (e.g., 76 rpm, 77 rpm, 78 rpm, 79 rpm, 80 rpm, 81 rpm, 82 rpm, 83 rpm, 84 rpm) for 30-60 minutes (e.g., 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes). Stirring at a stirring speed of 3 rpm or 84 rpm for 30–60 min (e.g., 35 min, 40 min, 45 min, 50 min, 55 min); preferably, the third stirring is: stirring at a stirring speed of 75–85 rpm (e.g., 76 rpm, 77 rpm, 78 rpm, 79 rpm, 80 rpm, 81 rpm, 82 rpm, 83 rpm, 84 rpm) and a dispersion speed of 6400–6600 rpm (e.g., 6450 rpm, 6500 rpm, 6550 rpm) for 60–90 min (e.g., 65 min, 70 min, 75 min, 80 min).

[0016] In the above-mentioned homogenization process of lithium-ion battery cathode slurry, as a preferred embodiment, the homogenization process further includes step S3: defoaming the cathode slurry prepared in step S2; preferably, the defoaming is: stirring at a speed of 10-20 rpm (e.g., 12 rpm, 14 rpm, 16 rpm, 18 rpm) for 20-40 min (e.g., 25 min, 30 min, 35 min).

[0017] In the above-mentioned homogenization process of lithium-ion battery cathode slurry, as a preferred embodiment, the homogenization process is carried out under a vacuum degree of <-90Kpa.

[0018] Secondly, the present invention provides a positive electrode slurry prepared by the above-mentioned homogenization process.

[0019] Thirdly, the present invention provides a lithium-ion battery, the battery comprising a positive electrode sheet prepared using the positive electrode slurry described in the second aspect above.

[0020] Compared with the prior art, the present invention has at least the following beneficial technical effects:

[0021] In the homogenization process of this invention, the adhesive solution is prepared by pre-spreading according to a specific solid content, ensuring uniform pre-dispersion of the adhesive solution and reducing the number of large particles in the slurry. It also achieves the kneading effect of dry processes, combining the advantages of both dry and wet processes. The homogenization process of this invention enables more uniform and fine dispersion of active particles, significantly reducing the probability of agglomeration, resulting in lower slurry viscosity and higher stability. Under the same raw material ratio, the homogenization process of this invention produces a higher solid content and better stability than the traditional wet homogenization process. Attached Figure Description

[0022] Figure 1 The viscosity of the slurry prepared for Example 1, Comparative Example 1, and Comparative Example 2 is plotted as a function of time. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0024] The embodiments of the present invention are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and processes are given. However, the protection scope of the present invention is not limited to the following embodiments. The process parameters in the following embodiments that do not specify specific conditions are generally in accordance with conventional conditions.

[0025] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0026] In this invention, unless otherwise specified and / or stated, all values ​​relating to component amounts are in parts by weight throughout. Process parameters in the following examples that do not specify particular conditions are generally performed under conventional conditions.

[0027] In the specific embodiments of the present invention, the stirring or mixing steps are all carried out in a double planetary mixer (volume 7.4L).

[0028] The present invention will be further described below with reference to specific embodiments, but this is not intended to limit the scope of protection thereof.

[0029] Implementation Example 1:

[0030] The theoretical solid content of the slurry in this example is 65% (the slurry includes 65 wt% cathode material and 35 wt% solvent NMP).

[0031] The specific cathode material formulation is as follows: binder: PVDF 2wt%, first conductive agent: super-P 0.5wt%, second conductive agent: CNT 0.7wt% (CNT solid content 5.1wt%, solvent is NMP), cathode active material: lithium iron phosphate (commercially purchased from Hubei Wanrun New Energy Technology Co., Ltd., model A8-4E), 96.8wt%.

[0032] First, pre-apply adhesive with a solid content of 5% (all PVDF and part NMP in the slurry formulation, the solid content of the adhesive after pre-applying is 5%), and stir in a double planetary mixer (volume 7.4L) for 120 minutes (stirring speed 80rpm + dispersion speed 4500rpm + vacuum less than -90KPa).

[0033] Divide the adhesive solution into three equal parts: first adhesive solution, second adhesive solution, and third adhesive solution. Add one-quarter of the mass of lithium iron phosphate and the first conductive agent (super-P) to the first adhesive solution and stir for 30 minutes (stirring speed 80 rpm + vacuum less than -90 kPa).

[0034] Next, add the second adhesive, the second conductive agent (CNT), and two-quarters of the mass of lithium iron phosphate, and stir for 30 minutes (stirring speed 80 rpm + vacuum less than -90 kPa only); finally, add the third adhesive, one-quarter of the mass of lithium iron phosphate, and the remaining NMP according to the designed solid content, stir for 90 minutes (stirring speed 80 rpm + dispersion speed 6500 rpm + vacuum less than -90 kPa), and defoam for 30 minutes (stirring speed 15 rpm only).

[0035] Comparison Example 1:

[0036] The theoretical solids content and specific formulation of the slurry in this comparative example are the same as those in Implementation Example 1.

[0037] (Wet process) First, pre-apply adhesive (PVDF+NMP) with a solid content of 5% and stir for 120 minutes (stirring speed 80 rpm + dispersion speed 4500 rpm + vacuum less than -90 kPa).

[0038] Add conductive agent (super-P) and conductive agent (CNT) to it, and stir for 60 minutes (stirring speed 80 rpm + dispersion speed 4500 rpm + vacuum less than -90 kPa).

[0039] Finally, add the positive electrode active material (lithium iron phosphate) and the remaining NMP, stir for 90 minutes (stirring speed 80 rpm + dispersion speed 6500 rpm + vacuum less than -90 kPa), and defoam for 30 minutes (stirring speed only 15 rpm).

[0040] Comparative Example 2:

[0041] The theoretical solids content and specific formulation of the slurry in this comparative example are the same as those in Implementation Example 1.

[0042] (Dry method) First, the conductive agent (super-P), conductive agent (CNT) and positive electrode active material are premixed and stirred for 30 minutes (stirring speed 30 rpm).

[0043] Add 78.15 wt% of all NMP and knead for 60 min (stirring speed 60 rpm).

[0044] Finally, add the remaining NMP and disperse at high speed for 120 minutes (stirring speed 60 rpm + dispersion speed 6500 rpm + vacuum less than -90 kPa), and defoam for 30 minutes (stirring speed only at 15 rpm).

[0045] Comparative Example 3:

[0046] This comparative example is basically the same as Implementation Example 1, except that this comparative example first pre-applies adhesive with a solid content of 3%.

[0047] Comparative Example 4:

[0048] This comparative example is basically the same as Implementation Example 1, except that this comparative example first pre-applies adhesive with a solid content of 7.5%.

[0049] Example of detection:

[0050] The viscosity, fineness, and solids content of the slurries prepared in Implementation Example 1 and Comparative Examples 1-4 were tested respectively. The test results are shown in Table 1 below. Figure 1 As shown.

[0051] Viscosity was tested using a viscometer (model: Lichen NDJ-5S) (100mL sample was taken, using a No. 64 rotor at 60 rpm). Timing was started from the time the slurry was discharged, and the viscosity changes of the slurry were measured at 0h, 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, and 16h. The test results are attached. Figure 1 As shown;

[0052] Fineness was measured using a fineness meter (instrument model: Shanghai Huake Experimental Equipment Co., Ltd. QXD (0~50 micrometers));

[0053] Solid content measurement method:

[0054] Take two clean petri dishes and dry them in a constant temperature oven at 105±2℃ for 30 minutes. Remove them and place them in a desiccator. After cooling to room temperature, weigh them to obtain the weight W of the petri dishes. Weigh 1-2g of the sample (slurry) into each of the two petri dishes with known constant weight, accurate to 0.001g, to obtain the accurate weight G of the sample.

[0055] After weighing the sample, spread it evenly on the bottom of the petri dish and bake it in a constant temperature oven at 160℃ for 30 minutes. Remove it and place it in a desiccator to cool to room temperature, then weigh it again. Repeat the aforementioned drying and weighing steps (baking in a constant temperature oven at 160℃ for 30 minutes, removing it and placing it in a desiccator to cool to room temperature, then weighing) until the weight difference between two consecutive weighings is no greater than 0.01 grams (all weighings are accurate to 0.01 grams). Take the last weighing result as the weight W1 of the baked sample and container. Two samples were measured in parallel.

[0056] Calculation method

[0057] The solid content % (X) is calculated using the following formula:

[0058] X = (W1 - W) / G × 100

[0059] In the formula:

[0060] X – Solid content of the slurry, in %;

[0061] W – Container weight, in grams;

[0062] W1—Weight of the sample and container after baking, in grams;

[0063] G – Sample weight, in grams.

[0064] The experimental results are taken as the average of two parallel experiments, and the relative error between the two average experiments is no greater than 3%.

[0065] Table 1

[0066]

[0067]

[0068] In the homogenization process of this invention, the adhesive solution is prepared by pre-spreading according to a specific solid content, so that the adhesive solution is pre-dispersed evenly, with fewer large particles in the slurry, while also having the kneading effect of dry processes. The homogenization process of this invention combines the advantages of both wet and dry processes, such as... Figure 1 As shown in Table 1, the solid content of the positive electrode slurry prepared in Example 1 of the present invention is higher than that of the wet process but lower than that of the dry process, and the stability of the slurry is superior to both the dry and wet processes.

[0069] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. However, any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A homogenization process for a lithium-ion battery cathode slurry, characterized in that, The positive electrode slurry includes a positive electrode material and a solvent, wherein the positive electrode material includes a positive electrode active material, a first conductive agent, a second conductive agent, and a binder; The homogenization process is as follows Includes the following steps: S1: Prepare a gel solution with a solid content of 5-7%. Mix all the binder in the positive electrode slurry with a portion of the solvent to prepare the gel solution. Divide the gel solution into 3 parts, namely the first gel solution, the second gel solution and the third gel solution. S2: Add 23-27 wt% of the total positive electrode active material and all of the first conductive agent to the first adhesive solution and stir for the first time. Then add the second adhesive solution, all of the second conductive agent and 45-55 wt% of the total positive electrode active material and stir for the second time. Finally, add the third adhesive solution, the remaining positive electrode active material and the remaining solvent and stir for the third time to obtain the positive electrode slurry. The first conductive agent is super-P; the second conductive agent is NMP conductive paste of carbon nanotubes.

2. The homogenization process as described in claim 1, characterized in that, In step S1, the adhesive solution is prepared with a solid content of 5.2% to 6.3%. And / or, the theoretical solid content of the positive electrode slurry is 60-66%; And / or, the positive electrode material comprises: 1.5~2.5wt% binder, 0.2~1.0wt% first conductive agent, 0.2~1.0wt% second conductive agent, and 96~97wt% positive electrode active material.

3. The homogenization process as described in claim 1 or 2, characterized in that, The adhesive is PVDF; And / or, the solvent is NMP; And / or, the solid content of the NMP conductive paste is 1~10%; And / or, the positive electrode active material is lithium iron phosphate or lithium nickel cobalt manganese oxide.

4. The homogenization process according to any one of claims 1-3, characterized in that, The mixing or stirring is carried out in a dual planetary mixer; And / or, in step S1, the mixing is: stirring at a stirring speed of 75~85 rpm and a dispersing speed of 4400 rpm~4600 rpm for 90~120 min; And / or, in step S1, the volume ratio of the first adhesive, the second adhesive, and the third adhesive is (0.8~1.2):(0.8~1.2):1; And / or, in step S2, the first stirring is: stirring at a stirring speed of 75~85 rpm for 30~60 min; And / or, in step S2, the second stirring is: stirring at a stirring speed of 75~85 rpm for 30~60 min; And / or, in step S2, the third stirring is: stirring at a stirring speed of 75~85 rpm and a dispersing speed of 6400~6600 rpm for 60~90 min; And / or, the homogenization process further includes step S3: defoaming the positive electrode slurry prepared in step S2.

5. The homogenization process as described in claim 4, characterized in that, The defoaming process involves stirring at a speed of 10-20 rpm for 20-40 minutes. And / or, in step S1, the volume ratio of the first adhesive, the second adhesive, and the third adhesive is 1:1:

1.

6. The homogenization process according to any one of claims 1-5, characterized in that, The homogenization process is carried out under a vacuum of <-90 kPa.

7. The positive electrode slurry prepared by the homogenization process according to any one of claims 1-6.

8. A lithium-ion battery, characterized in that, The battery includes a positive electrode sheet prepared using the positive electrode slurry according to claim 7.

Citation Information

Patent Citations

  • Preparation method of positive electrode thick liquid of lithium battery

    CN105552359A

  • Preparation method of high-rate lithium ion battery anode slurry

    CN106207129A

  • Preparation method of positive electrode slurry of lithium battery

    CN111599987A